Comparison of neurosensory devices in detecting cutaneous thresholds related to protective sensibility: A cross-sectional study in São Paulo, Brazil. (November 2019) - Carvalho, V.F.; Ueda, T.; Paggiaro, A.O.; Nascimento, A.R.F.; Ferreira, M.C.; Gemperli, R.
Abstract: Aims: To quantify the static and moving cutaneous sensibility threshold of diabetic patients using a neurosensory device for quantitative pressure detection. Methods: Three hundred thirty-four (n = 334) patients with type 2 diabetes and no previous history of wounds on the feet were studied using the one- and two-point static (1SP;2 SP) and one- and two-point moving (1MP;2 MP) tests through the pressure-specified sensory device (PSSD) on the cutaneous territory of the dorsal first web, hallux pulp, and medial calcaneal. In addition, patients were evaluated using the Semmes-Weinstein monofilament (SWM) No. 5.07 and tuning fork (128 Hz), which were used as normality parameters to detect the loss of protective sensibility. The same examinations were used to assess the control group (228 nondiabetic). Results: Altered values were observed for the static and moving tests over the three studied nerve territories. In comparing the sensibility threshold between diabetic patients who were sensitive and nonsensitive to SWM 5.07, we observed that this filament is not the most indicated for identifying the loss of sensibility in these patients. The prevalence of patients at risk varied between 85 and 89%. The biochemical marker associated with these high rates was HbA1c (p = 0.02). Conclusions: Numeric quantification of the pressure threshold allowed us to determine the functional deficit of nerve fibers. Our findings suggest that the neurosensory device should be used as an adjuvant tool to evaluate the degree of loss of sensation on the skin.